Autonomic dysfunction and migraine: Assessed by time series analysis of heart rate variability - Tahmina Akter Sultana Ferdousi; Sultana Ferdousi (Journal of Bangladesh Society of Physiologists, 2018)
Background: Migraine is associated with autonomic nervous system dysfunction with reduced heart rate variability (HRV).